2012
DOI: 10.1179/1743284712y.0000000095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on microstructure and mechanical properties of extruded ZM61 magnesium alloy

Abstract: The effects of T5 and T6 heat treatments on the microstructure and mechanical properties of extruded Mg–6Zn–1M n alloy were investigated in the present study. The results showed that T5 and T6 treatments could markedly improve the strengths of extruded ZM61 alloy, and the precipitate strengthening effect of double aging was better than that of single aging. The precipitates formed in the T6 treatment were much finer and more dispersive than the ones in the T5 treatment, resulting in stronger precipitation stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It is observed that two kinds of precipitates formed during aging treatment. It has been reported [16][17][18][22][23][24] that the two precipitates are rod shaped b' 1 and plate shaped b' 2 precipitates, respectively. Most of the precipitates in single aged alloy are rod shaped b' 1 with a dimension of 100 nm in length and 10 nm in width.…”
Section: Microstructuresmentioning
confidence: 98%
See 1 more Smart Citation
“…It is observed that two kinds of precipitates formed during aging treatment. It has been reported [16][17][18][22][23][24] that the two precipitates are rod shaped b' 1 and plate shaped b' 2 precipitates, respectively. Most of the precipitates in single aged alloy are rod shaped b' 1 with a dimension of 100 nm in length and 10 nm in width.…”
Section: Microstructuresmentioning
confidence: 98%
“…[11][12][13][14][15] According to our previous researches, after T6 treatment (solution treatment and double aging), the yield strength (YS), ultimate tensile strength (UTS) and elongation of ZM61 could reach more than 340 MPa, 370 MPa and 5%, respectively. 16 The age hardening response of ZM61 alloy is mainly from Mg-Zn intermetallic compounds, rod shaped b' 1 precipitates are the key age hardening precipitates while extensive precipitation of plate shaped b' 2 phase causes overaging. 17,18 By reason of the method to estimate fracture toughness is difficult, high cost and always time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, low absolute strength and poor formability have become the bottleneck which constrains Mg alloys application. [3][4][5][6] Currently, many researchers have performed a role in the development of high-strength wrought Mg alloys. Alloying has been widely used as one of the most effective ways to develop new high-strength wrought Mg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…5 Alloying addition is an effective method to improve the microstructure and mechanical properties of magnesium alloys. 6 Sn, as an additional element to magnesium alloys, is of great importance due to its cheap price and potential to develop mechanical properties. 7 This element forms thermally stable Mg 2 Sn phase with a face centre cubic structure.…”
Section: Introductionmentioning
confidence: 99%